If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + -5d = d Solving 25 + -5d = d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-1d' to each side of the equation. 25 + -5d + -1d = d + -1d Combine like terms: -5d + -1d = -6d 25 + -6d = d + -1d Combine like terms: d + -1d = 0 25 + -6d = 0 Add '-25' to each side of the equation. 25 + -25 + -6d = 0 + -25 Combine like terms: 25 + -25 = 0 0 + -6d = 0 + -25 -6d = 0 + -25 Combine like terms: 0 + -25 = -25 -6d = -25 Divide each side by '-6'. d = 4.166666667 Simplifying d = 4.166666667
| -30(-5)= | | 2(-4)(-6)= | | (-14)2= | | 3x+5(x-7)=41 | | (6)(-8)= | | 0.80x+0.50(8-x)=.10(-101) | | 2g-2+4g-9= | | Y=X[X-4] | | -21=x+10 | | (-6)(-9)= | | X-19=-43 | | 90+2x+x+15=180 | | (-2)(8)= | | 2x-9y-4=0 | | 3x^2+2x=12 | | 4-2x=5-x-1 | | .05d-3d+5=0 | | X+12+x=44 | | -4[X+2]=3[2X+1] | | 2(2x-3)=x+3(x-6) | | 6(x-2)=4-2x | | 4x^2+6x-8x^2=5 | | y=-1.3x-2 | | 13-2x=25 | | c^2=196 | | -5(a+6)=2(3a+8) | | 64=x+32 | | 6x^2+27x=15 | | 6x-7=-4x+4 | | 2(p-q)=r | | 3x-4+2x+8=8x-14 | | 25a^2-10a+8=0 |